Anatomical analysis of zygomatic bone in ectodermal dysplasia patients with oligodontia. (21st February 2019) - Wang, Haowei; Hung, Kuofeng; Zhao, Kai; Wang, Yueping; Wang, Feng; Wu, Yiqun
Abstract: Background: Abnormalities of some facial bones derived from the ectomesenchyme have been found in ectodermal dysplasia (ED) patients, but the characteristics of the zygoma are unknown. Purpose: Comparison between ED patients and normal individuals to understand the anatomical features of the zygoma in ED patients. Materials and Methods: Thirty patients diagnosed with ED based on clinical features and/or gene sequence tests and 80 normal individuals were recruited from 2016 to 2018. The thickness of the zygomatic body at 12 points on the superior, middle, and inferior areas and the length of four lines were measured on a three‐dimensional cone beam computed tomography image. Differences between ED patients and normal individuals were then compared. Results: The zygomatic thicknesses and lengths were smaller in ED patients than in normal individuals. For ED patients, the largest thicknesses on the superior, middle, and inferior areas of the zygoma were 8.47 ± 1.49, 7.03 ± 1.56, and 5.99 ± 1.22 mm. Conclusion: The development of zygomatic thickness on the inferior area and the zygomatic length were insufficient in ED patients with oligodontia. Consequently, zygomatic hypoplasia presented difficulties for the "quad approach" to zygomatic implants in this group of patients.